2015
DOI: 10.1097/bco.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

An update on distal biceps tendon ruptures

Abstract: The incidence of distal biceps ruptures is 1.2/100,000 people per year. It is most commonly seen in men 40--60 yr old involving their dominant arm. The mechanism of injury is the application of an eccentric load to the elbow region. Some report a preceding tendinitis, which speaks to the degenerative changes and decrease in vascularity as contributing factors to the tendon rupture. Nonoperative treatment is an option. However, most younger, healthy, and active patients benefit from early surgical management to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Furthermore, the high complication rate reported in the current literature associated with operative treatment calls into question the superiority of operative versus nonoperative approaches. 1,6,7,12,14 As such, the optimal treatment for complete and partial DBBT ruptures remains controversial, 1,3 5,7 9,12,15,16 with some evidence suggesting favorable outcomes in low-demand or unhealthy patients treated nonoperatively. 4,8 This is supported by the current study wherein patients with complete and partial DBBT ruptures treated operatively and nonoperatively maintained satisfactory clinical and functional outcomes at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the high complication rate reported in the current literature associated with operative treatment calls into question the superiority of operative versus nonoperative approaches. 1,6,7,12,14 As such, the optimal treatment for complete and partial DBBT ruptures remains controversial, 1,3 5,7 9,12,15,16 with some evidence suggesting favorable outcomes in low-demand or unhealthy patients treated nonoperatively. 4,8 This is supported by the current study wherein patients with complete and partial DBBT ruptures treated operatively and nonoperatively maintained satisfactory clinical and functional outcomes at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,7,12,14 As such, the optimal treatment for complete and partial DBBT ruptures remains controversial, 1,3 5,7 9,12,15,16 with some evidence suggesting favorable outcomes in low-demand or unhealthy patients treated nonoperatively. 4,8 This is supported by the current study wherein patients with complete and partial DBBT ruptures treated operatively and nonoperatively maintained satisfactory clinical and functional outcomes at final follow-up. However, the majority of patients presenting with complete or partial DBBT tears still opt for operative treatment, which may be inherent to a subsequent Popeye deformity and cosmetic reasons, rather than true functional deficit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a rehabilitation perspective, it has been suggested that unrestricted or early range of motion may begin earlier since repair strength is greater than the force of an unweighted forearm in a splint or brace. [19][20][21] Restrictions typically include lifting no more than five pounds and no supination against resistance. At six weeks, gradual strengthening of the upper extremity and aerobic conditioning may begin.…”
Section: Introductionmentioning
confidence: 99%
“…
Distal biceps tendon (DBT) ruptures account for nearly 10% of all biceps tendon ruptures [1][2][3][4], with an incidence of 2.55 per 100,000 patients per year reported in the US [5]. The majority occur in men between 40 and 60 years old, with a greater incidence among manual workers, weight-lifters, and athletes [3,6]. Recent epidemiological studies found a similar prevalence between dominant and non-dominant arms [7].
…”
mentioning
confidence: 99%